Surviving or thriving? Unraveling the business resources enabling competitive advantage in locally owned bridal boutiques - Ishtehar Sharif Swazan; Debanjan Das; Melissa Sherfinski (Cogent Business & Management, 2023)
Bridal boutiques quickly became the most popular bridal business as bridal dress is considered the biggest priority for any bride. To capture this market, many locally-owned bridal boutiques were established within U.S. local communities, subsequently becoming integral to the economic fabric by fostering entrepreneurship and generating employment opportunities. Our study aims to explore the resources possessed by these businesses in this post-pandemic period and how these resources are assisting in achieving competitive advantage. Qualitative semi-structured interviews were carried out for this study, and Resource-Based Theory (RBT) was used as the conceptual framework. The study findings unveiled that the knowledge and experience of business owners emerged as a vital resource, enabling boutique owners to effectively steer their businesses right from their inception. The study findings contributed to the existing body of small fashion/apparel business literature by presenting novel evidence regarding the competitive advantage of local bridal boutiques.
Keywords: 650; bridal boutique; competitive advantage; fashion retail; resource-based theory; retail management; U.S. local business